Faktor – Faktor yang Mempengaruhi Audit Delay (Studi Empiris Pada Perusahaan Manufaktur yang Terdaftar di BEI 2006-2010) (Students' Journal of Accounting and Banking, 2012)
This research purpose to empirically examined the influence of size of the company, profit / loss surgery, auditor opinion, auditor reputation, and solvency toward audit delay of the listed manufacture companies in Indonesia Stock Exchange.This study focuses on manufacturing firms. The data used are secondary data, namely the 381 sample companies listed on the Indonesia Stock Exchange in the year 2006 to 2010. Analysis tool used is multiple regression.The test results of the test statistic is t show a profit / loss operation significantly negative effect on audit delay. While the size of the company, auditor opinion, auditor reputation and solvency has no effect on audit delay.Keywords: audit delay, size of the company, profit / loss operation, auditor opinion, auditor reputation, solvency.